Giovani, educazione e democrazia in Israele. La prospettiva di «New Outlook» negli anni Sessanta - Simoni, Marcella (SocietàMutamentoPolitica, 2012)
In the Israeli-Palestinian conflict context, education can be an instrument of change and democratization. “New Outlook” journal is a paradigmatic experience of mutual cooperation. “New Outlook” enables “dissociation” and “association” dynamics, promoting a decostruction of national narration and the making of an alternative narration, based upon the living together of new generations.